Factor structure and convergent validity of the Derriford Appearance Scale-24 using standard scoring versus treating 'not applicable' responses as missing data: a Scleroderma Patient-centered Intervention Network (SPIN) cohort study. Issue 3 (6th March 2018) - Merz, Erin L; Kwakkenbos, Linda; Carrier, Marie-Eve; Gholizadeh, Shadi; Mills, Sarah D; Fox, Rina S; Jewett, Lisa R; Williamson, Heidi; Harcourt, Diana; Assassi, Shervin; Furst, Daniel E; Gottesman, Karen; et al.
Abstract : Objective: Valid measures of appearance concern are needed in systemic sclerosis (SSc), a rare, disfiguring autoimmune disease. The Derriford Appearance Scale-24 (DAS-24) assesses appearance-related distress related to visible differences. There is uncertainty regarding its factor structure, possibly due to its scoring method. Design: Cross-sectional survey. Setting: Participants with SSc were recruited from 27 centres in Canada, the USA and the UK. Participants who self-identified as having visible differences were recruited from community and clinical settings in the UK. Participants: Two samples were analysed (n=950 participants with SSc; n=1265 participants with visible differences). Primary and secondary outcome measures: The DAS-24 factor structure was evaluated using two scoring methods. Convergent validity was evaluated with measures of social interaction anxiety, depression, fear of negative evaluation, social discomfort and dissatisfaction with appearance. Results: When items marked by respondents as 'not applicable' were scored as 0, per standard DAS-24 scoring, a one-factor model fit poorly; when treated as missing data, the one-factor model fit well. Convergent validity analyses revealed strong correlations that were similar across scoring methods. Conclusions: Treating 'not applicable' responses as missing improved the measurement model, but did not substantively influence practical inferences that can be drawn from DAS-24 scores. Indications of item redundancy and poorly performing items suggest that the DAS-24 could be improved and potentially shortened.